Implementation of Murajaah Method in Memorizing Quran at MTA Zainul Ibad: Indonesia - Hamzah Maimunah; Agus Kharir (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to determine the process of implementing the muraja'ah method in memorizing the AL-Qur'an which is applied to MTA Zainul Ibad students. The approach used in this research is a qualitative approach with the type of research field research (field research). Then use primary and secondary data as research material. Meanwhile, to obtain the data, researchers used interview, observation, and documentation techniques. In this case, the researcher analyzes using data reduction techniques, data presentation, and data verification. The result of the research is that the Muraja'ah form of memorizing the Koran that is applied in MTA Zainul Ibad is divided into three, namely: muraja'ah individually, muraja'ah with friends, and muraja'ah with ustad and chaplain, the process is applied so that the quality of memorizing each The students are always awake and not easily forgotten. So to find out the result of memorization, a Muhafiz performs a muraja'ah test by re-listening to the memorization of his students. So it can be proven that at MTA Zainul Ibad is very disciplined towards his students' muraja'ah memorization. All of that is applied on the basis of the importance of repeating the memorization of the Al-Qur'an because a memorizer of the AL-Qur'an will always be tied to the Al-Qur'an throughout his life.